The Violation of Conversational Maxims in the Movie Series Divergent - Adelia Fatmawati Pradani; Thomas Joko Priyo Sembodo (Lexicon, 2020)
This research focuses on identifying the types of conversational maxims violated by the characters in a feature film trilogy entitled The Divergent Series. This research also aims to explain the functions of the violation of conversational maxims in the series. The result shows that there are 100 violations of conversational maxim in Divergent series, and among those, there are 43 violations of maxim of relevance (43%), which is the most frequently occurred in the movie. The second violation identified is the violation of maxim of manner, which reaches 24 violations (24%), and the third frequently occurring violation is violations of maxim of quantity with 22 numbers of violation (22%)/. The least occurring violation found in the movie is violation of  maxim of quality, which reaches 11 numbers of violation (11%). There are several functions of the violation of conversational maxim found in the movie: keeping a secret, concealing half of the information, avoiding certain topic/question, and confusing the hearer.